On hairpin vortices in a transitional boundary layer - Uruba Václav; Jonáš Pavel; Hladík Ondřej (EPJ Web of Conferences, 2012)
In the presented paper the results of experiments on transitional boundary layer are presented. The boundary layer was generated on smooth flat wall with zero pressure gradient forming one side of the channel of rectangular cross section. The hairpin vortices, packets of hairpin vortices, turbulent spots and calmed regions were experimentally investigated using time-resolved PIV technique.